Nilai–Nilai Pendidikan Karakter dalam Kitab Kifayat Al-Atqiya - Rudiana, Randi; Husni, Husni (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
Kifayat al-Atqiya is a book guide the work of scholars sufi ash bakri al-makki, took to any muslim to be the good to completely in view of Alloh and in the teach through a touch tasawuf manner. Who become the focus of this research is on value education character written in the book Kifayat al-Atqiya ash bakri al-makki. His study the formulation of the problem and the goal is to:1. Study characters who are in the book Kifayatul al-Atqiya ash bakri al-makki and 2. Implementation value of education characters who are in the book kifayat al-Atqiya ash bakri al makki with education islam contemporary. This study is the research study diving manual (library research). The writer trying to examine the values ​​of education characters who are in the book Kifayat al-Atqiya Abu Bakri al-Makki. The techniques data collection by way of digging ingredients divining that koheren and relevant to the object discussion of the be assessed. As for the used is hermeuneutic. While his analysis using the concept of heremeneutika Paul Ricoeur by the way to identify verse form using Kifayat al-Atqiya with the value of education character, to then interprete and understanding of the text (textual exegesi). The results of research conducted, be fruitless as follows: ( 1 ) Of the values ​​of education of the characters in the book Kifayat al-Atqiya is taubat, qana’ah, zuhud, tawakal, sincere, uzlah, keep the time, The values ​​of education character contained in the book “Kifayat al-Atqiya” in focus oriented coaching manners that are holistic which consists of manners to Allah Swt. ( habl min Allah), and manners against other people ( habl min al-nas ), which includes a maintain oral from the conversation who hurt other people. All the values ​​of education of the characters in the book “Kifayat al-Atqiya” reflect the character overall covering the dimensions of divinity and dimensions social. ( 2 ) Implementation of education values character in the book Kifayat al-Atqiya with the Islamic religion contemporary education is to use the approach, among others: The planting value, approach to cognitive development, the analysis of the value, the clarification value, the learning do.